Presentation Skills for Scientists with DVD-ROM - Edward D Zanders (Cambridge University Press, 2010)
Scientists are rarely given formal training in presentation skills and yet are often called upon to present the results of their research. This book provides a practical guide to the creation and delivery of scientific presentations, whatever the topic. Its practical 'how-to' style leaves discussion of the background psychology of public speaking to others and focuses instead on the issues that are of immediate concern to the busy scientist. The text covers all of the important aspects of scientific presentations, ranging from audience awareness to handling questions. Links are included throughout the text to the accompanying DVD, which contains annotated video clips of speakers delivering a talk and demonstrates the common problems found with many presenters, as well as the exercises designed to overcome them. Image files of different slide layouts, colour schemes and font styles demonstrate the design issues that one must consider when creating visual material.